EFEKTIVITAS PENGGUNAAN PEMBELAJARAN MENGGUNAKAN MASALAH PADA MATERI EKOSISTEM KELAS V SD NEGERI ROGOMULYO 01 - Siti Khalimatul Aminah; Nur Fajrie; Irfai Fathurohman (Journal Prakarsa Paedagogia, 2024)
The history of the issue 57% students unable to reached KKM score caused by the low understanding and motivation of students towards learning Natural Sciences (IPA). This study's goal to outline the cognitive system thinking of ecosystem material through the PBL model in grade V SD. Location of the research was SD Negeri Rogomulyo 01. There were 21 students involved in this study as research subjects. Techniques for gathering data included observations and interviews. One method of gathering data is by administering an exam to students in grade V. Both quantitative and qualitative analysis was the method of data analysis employed. The findings demonstrated: (1) problem orientation; (2) student organization; (3) directing investigations; (4) creating and presenting data; and (5) analysis and evaluation. The average student activity increased from 43% (cycle I) to 98% (cycle II) from the initial condition, potentially improving student learning outcomes. Students' cognitive capacities regarding ecosystems material through the problem Based Learning learning model are in in keeping with the phases of cognitive reasoning.